The Influence of Hydrogen on the Properties of Zinc Sulfide Thin Films Deposited by Magnetron Sputtering. (7th April 2014) - Xu, Hang; Wu, Lili; Wang, Wenwu; Zhang, Lixiang; Zhang, Jingquan; Li, Wei; Feng, Lianghuan
Abstract : Zinc sulfide thin films have been deposited with hydrogen in Ar and Ar+H2 atmosphere by radio frequency magnetron sputtering. The thickness, structural properties, composition, surface morphology, and optical and electrical properties of the films have been investigated. Effect of hydrogen on the properties of the film was studied. The results showed that hydrogen leads to better crystallinity and larger crystallite size of ZnS polycrystalline films. The band gaps of the films in Ar+H2 are about 3.48 eV compared with 3.24 eV without hydrogen. It is also demonstrated that hydrogen can result in a better stoichiometric composition of the films.